Berberine Prevents Disease Progression of Nonalcoholic Steatohepatitis through Modulating Multiple Pathways - Yanyan Wang; Yun-Ling Tai; Derrick Zhao; Yuan Zhang; Junkai Yan; Genta Kakiyama; Xuan Wang; Emily C. Gurley; Jinze Liu; Jinpeng Liu; Jimin Liu; Guanhua Lai; et al. (Cells, 2021)
Background and Aims: The disease progression of nonalcoholic fatty liver disease (NAFLD) from simple steatosis (NAFL) to nonalcoholic steatohepatitis (NASH) is driven by multiple factors. Berberine (BBR) is an ancient Chinese medicine and has various beneficial effects on metabolic diseases, including NAFLD/NASH. However, the underlying mechanisms remain incompletely understood due to the limitation of the NASH animal models used. Methods: A high-fat and high-fructose diet-induced mouse model of NAFLD, the best available preclinical NASH mouse model, was used. RNAseq, histological, and metabolic pathway analyses were used to identify the potential signaling pathways modulated by BBR. LC–MS was used to measure bile acid levels in the serum and liver. The real-time RT-PCR and Western blot analysis were used to validate the RNAseq data. Results: BBR not only significantly reduced hepatic lipid accumulation by modulating fatty acid synthesis and metabolism but also restored the bile acid homeostasis by targeting multiple pathways. In addition, BBR markedly inhibited inflammation by reducing immune cell infiltration and inhibition of neutrophil activation and inflammatory gene expression. Furthermore, BBR was able to inhibit hepatic fibrosis by modulating the expression of multiple genes involved in hepatic stellate cell activation and cholangiocyte proliferation. Consistent with our previous findings, BBR’s beneficial effects are linked with the downregulation of microRNA34a and long noncoding RNA H19, which are two important players in promoting NASH progression and liver fibrosis. Conclusion: BBR is a promising therapeutic agent for NASH by targeting multiple pathways. These results provide a strong foundation for a future clinical investigation.